2001
DOI: 10.1590/s1517-83822001000300012
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pcb01, a Plasmid for Dna Immunization Against the Adhesin of Escherichia Coli K88ab

Abstract: Growth characteristics and plasmid yields of Escherichia coli JM109 transformed with pCB01, a plasmid that encodes genes for the fimbrial adhesin of E. coli K88ab and for ampicillin resistance, grown in two culture media in agitated flasks and in fermentor, are reported. The rate of plasmid loss during growth was estimated by the differential counts in media with and without ampicillin. Plasmid yields of cultures grown in flasks varied from 0.9 to 67 µg/ml of medium, while those grown in fermentor attained 62 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This phenomenon was unlikely to have resulted from loss of the eGFPuv plasmid during the 30-day pupal stage (on the contrary, unpublished data from our laboratory indicated that recSodalis bacteria grown in vitro retained their plasmids in the absence of antibiotic selection over a 3-month test period). Oxygen deprivation in the sealed environment of the tsetse fly's pupal case more likely accounted for our inability to consistently detect this gene (although very faint bands were present in some samples), as the replication and stability of plasmids carrying ColE1 replication origins (i.e., pGFPuv) can be severely impeded under such conditions (15,20). We are currently developing a method of inserting exogenous DNA directly into the Sodalis chromosome via homologous recombination.…”
Section: Fig 2 Growth Rates Of Recombinant Sodalis Glossinidius Mormentioning
confidence: 99%
“…This phenomenon was unlikely to have resulted from loss of the eGFPuv plasmid during the 30-day pupal stage (on the contrary, unpublished data from our laboratory indicated that recSodalis bacteria grown in vitro retained their plasmids in the absence of antibiotic selection over a 3-month test period). Oxygen deprivation in the sealed environment of the tsetse fly's pupal case more likely accounted for our inability to consistently detect this gene (although very faint bands were present in some samples), as the replication and stability of plasmids carrying ColE1 replication origins (i.e., pGFPuv) can be severely impeded under such conditions (15,20). We are currently developing a method of inserting exogenous DNA directly into the Sodalis chromosome via homologous recombination.…”
Section: Fig 2 Growth Rates Of Recombinant Sodalis Glossinidius Mormentioning
confidence: 99%
“…E. coli mcrA + grew at μ control = 0.16 h -1 , μ FISH-TAMB = 0.14 h -1 whereas E. coli pmoA + grew at μ control = 0.14 h -1 , μ FISH-TAMB = 0.12 h -1 . These decreased growth rates relative to plasmid-free E. coli (Sezonov et al , 2007; Gil-Turnes et al , 2001) indicated growth inhibitory effects of the mcr A and pmo A inserts and hinted the difficulty of expressing mcr A in E. coli for FISH-TAMB detection. Doubling times for both control and FISH-TAMB-treated M. barkeri were ∼ 21 hours (μ = 0.03 h -1 ), which are consistent with previous reports of hydrogenotrophic M. barkeri growth (Maestrojuan and Boone, 1991).…”
Section: Resultsmentioning
confidence: 99%